IMPLEMENTATION OF TOPSIS METHOD SELECTION OF STUDENT ACHIEVEMENT LANE STMIK PRINGSEWU - Sucipto Sucipto; Deni Kurniawan Wibisono (STMIK Pringsewu Lampung, 2019)
New admissions is a routine activity carried out by all universities in Indonesia each year. These activities may be regarded as the starting point of the search process for new students STMIK Pringsewu quality. At this time the data processing for selecting new students achievement lane STMIK Pringsewu still using Microsoft Excel. The processing of value requires a long time, especially in the process of selection and ranking process. Decision support system is the right system to be implemented, because the decision support system can help make decisions based on the same criteria. The method used in this research is the method of TOPSIS (Technique for Order Preference by Similarity to Ideal Solution). Selection of new students STMIK Pringsewu using TOPSIS method. results of a decision support system using the method of TOPSIS (Technique for Order Preference by Similarity to Ideal Solution)to assist and facilitate Universities in determining which students are competent or not get into college STMIK Pringsewu use the path of achievement.